Efektivitas Kegiatan Keagamaan Dalam Perilaku Siswa - Muhammad Azifatul Anwar; Muhammad Zaim; Muhammad Faisal (Al-Mada: Jurnal Agama, Sosial, dan Budaya, 2023)
Religious activities are a must in applying Islamic religious education materials in schools that can develop the quality of students and means of da'wah. As well as an aspect of religious habituation that embodies the development of students toward knowledge and personality attitudes that are in accordance with Islamic religious worship. The implementation of religious activities that are applied contains the value of goodness towards Allah SWT and fellow human beings. Religious activities are an alternative to creating the character and personality of religious students at school. This study aims to describe the effectiveness of religious activities in student behavior at SMPN 14 Banjarbaru. This study uses a quantitative approach with the type of field research (field research). Sources of data obtained from teachers and students then conclude in accordance with the results of the calculation of the questionnaire that belongs to the interpretation of the percentage. The results showed that the effectiveness of religious activities in schools at SMPN 14 Banjarbaru was in the "Effective" category with a percentage of 78.9%. Religious activities also provide character and personality formation that can motivate people to act in participate in these activities. And of course, these activities can be blessed by God.